Kinesin-1 and mitochondrial motility control by discrimination of structurally equivalent but distinct subdomains in Ran-GTP-binding domains of Ran-binding protein 2. Issue 3 (March 2013) - Patil, Hemangi; Cho, Kyoung-in; Lee, James; Yang, Yi; Orry, Andrew; Ferreira, Paulo A.
Abstract : The pleckstrin homology (PH) domain is a versatile fold that mediates a variety of protein–protein and protein–phosphatidylinositol lipid interactions. The Ran-binding protein 2 (RanBP2) contains four interspersed Ran GTPase-binding domains (RBD n = 1–4 ) with close structural homology to the PH domain of Bruton's tyrosine kinase. The RBD2, kinesin-binding domain (KBD) and RBD3 comprise a tripartite domain (R2 KR3 ) of RanBP2 that causes the unfolding, microtubule binding and biphasic activation of kinesin-1, a crucial anterograde motor of mitochondrial motility. However, the interplay between Ran GTPase and R2 KR3 of RanBP2 in kinesin-1 activation and mitochondrial motility is elusive. We use structure–function, biochemical, kinetic and cell-based assays with time-lapse live-cell microscopy of over 260 000 mitochondrial-motility-related events to find mutually exclusive subdomains in RBD2 and RBD3 towards Ran GTPase binding, kinesin-1 activation and mitochondrial motility regulation. The RBD2 and RBD3 exhibit Ran-GTP-independent, subdomain and stereochemical-dependent discrimination on the biphasic kinetics of kinesin-1 activation or regulation of mitochondrial motility. Further, KBD alone and R2 KR3 stimulate and suppress, respectively, multiple biophysical parameters of mitochondrial motility. The regulation of the bidirectional transport of mitochondria by either KBD or R2 KR3 is highly coordinated, because their kinetic effects are accompanied always by changes in mitochondrial motile events of either transport polarity. These studies uncover novel roles in Ran GTPase-independent subdomains of RBD2 and RBD3, and KBD of RanBP2, that confer antagonizing and multi-modal mechanisms of kinesin-1 activation and regulation of mitochondrial motility. These findings open new venues towards the pharmacological harnessing of cooperative and competitive mechanisms regulating kinesins, RanBP2 or mitochondrial motility in disparate human disorders.